2021
DOI: 10.3389/fimmu.2021.777851
|View full text |Cite
|
Sign up to set email alerts
|

Digenic Inheritance: Evidence and Gaps in Hemophagocytic Lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory disorder characterized by the inability to properly terminate an immune response. Familial HLH (FHLH) and related immune dysregulation syndromes are associated with mutations in the genes PRF1, UNC13D, STX11, STXBP2, LYST, AP3B1, and RAB27A, all of which are required for the assembly, exocytosis, and function of cytotoxic granules within CD8+ T cells and natural killer (NK) cells. Loss-of-function mutations in these genes render the cytotoxicity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…Variation in HLH genes causes congenital HLH in a recessive fashion, but it has also been suggested variants in different HLH genes could synergize to cause pathology in a digenic or oligogenic fashion. 9 We examined the set of variants that were observed in these combinations (Table 1, Supplementary Data 4) and observed that most combinations involved LYST in both cases and controls. However combinations involving LYST occurred significantly more commonly in sJIA (11/481, 2.2%) than in controls (24/2924, 0.8%; p = 0.007; OR 2.8 [1.2,6.0]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in HLH genes causes congenital HLH in a recessive fashion, but it has also been suggested variants in different HLH genes could synergize to cause pathology in a digenic or oligogenic fashion. 9 We examined the set of variants that were observed in these combinations (Table 1, Supplementary Data 4) and observed that most combinations involved LYST in both cases and controls. However combinations involving LYST occurred significantly more commonly in sJIA (11/481, 2.2%) than in controls (24/2924, 0.8%; p = 0.007; OR 2.8 [1.2,6.0]).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the hypothesis that variants in LYST , which is involved in granule biosynthesis and generally leads to milder cytolytic defects, may interact with heterozygous variants in terminal granule processing genes and produce pathology. 9…”
Section: Discussionmentioning
confidence: 99%
“…This may partly be due to the unavailability of genetic testing in all patients but one. Notably, no sharp demarcation exists between primary and secondary HLH, since primary HLH is often initiated by an infection or other trigger [5] and secondary HLH is often associated with a genetic predisposition [6].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines including interleukin (IL)‐1, IL‐6, tumour necrosis factor, and IL‐18 perpetuate systemic hyperinflammation, resulting in tissue damage, multi‐organ failure and death 1–3 . Classically, familial HLH presents in infancy with subtypes defined by specific germline variants driving immune dysfunction 4 . Secondary HLH (sHLH), also referred to as macrophage activation syndrome (MAS) in the context of rheumatological disease, is often sporadic presenting at any age, usually associated with an immunological trigger such as a systemic infection, underlying rheumatological/autoimmune disease or malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Classically, familial HLH presents in infancy with subtypes defined by specific germline variants driving immune dysfunction. 4 Secondary HLH (sHLH), also referred to as macrophage activation syndrome (MAS) in the context of rheumatological disease, is often sporadic presenting at any age, usually associated with an immunological trigger such as a systemic infection, underlying rheumatological/autoimmune disease or malignancy. Clinical recognition of sHLH/MAS can be challenging, with no single pathognomonic feature and a wide spectrum of severity.…”
Section: Introductionmentioning
confidence: 99%